Faces do imaginário Amazônico em Macunaíma, de Mário de Andrade - Muniz, Ângela Maria Lima (2016)
The main aim this study was to analyze beings of the regional mythology and folklore present in the Macunaíma rhapsody, the hero without any personality, written by Mário de Andrade. To understand better these characters, it was necessary to investigate the origin of the Amazon tribe’ women, Curupira and Uiara and to relate, if possible, these beings With Greek mythology. This way, it was possible to observe them according to filmmaker Joaquim Pedro de Andrade‘s point of view in the Macunaíma film. To that end, the theoretical contribution was related to readings about the theme on study, such as The Holanda (1977); Proença (1978); Gondim (2007); Krüger (2005); Eliade (1986); Mielietinski (1987), among others. Besides, this study has had a bibliographic approach and the orientations presented were based on the research line Comprehension of the Literary Work of the Postgraduate Course in Letters and Arts of the State University of Amazonas - PPGLA-UEA. Finally, we have the final product, entitled Macunaíma’s Toponymic Dictionary, which describes the route of the places covered by Macunaíma in the rhapsody written by Mário de Andrade. Keyword: Imaginary; Myth; Folklore; Macunaíma character; Macunaíma’s Toponymic Dictionary.